2011
DOI: 10.1073/pnas.1107038108
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity to social reputation in autism

Abstract: People act more prosocially when they know they are watched by others, an everyday observation borne out by studies from behavioral economics, social psychology, and cognitive neuroscience. This effect is thought to be mediated by the incentive to improve one's social reputation, a specific and possibly uniquely human motivation that depends on our ability to represent what other people think of us. Here we tested the hypothesis that social reputation effects are selectively impaired in autism, a developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
169
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(195 citation statements)
references
References 39 publications
23
169
3
Order By: Relevance
“…It is of course possible that, as a result of social desirability effects, the low AQ group in fact made more pro-social choices in this task than they would actually display in real life. By contrast, the high AQ group might have been more honest in describing their real-life actions, since individuals with ASD have been found to display diminished sensitivity to protecting their social reputations (Izuma et al 2011). Nevertheless, the use of everyday-type scenarios is undoubtedly of greater ecological validity than more traditional abstract tasks, and the clinical evidence suggests that reduced pro-social behaviour is likely to characterise everyday performance in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of course possible that, as a result of social desirability effects, the low AQ group in fact made more pro-social choices in this task than they would actually display in real life. By contrast, the high AQ group might have been more honest in describing their real-life actions, since individuals with ASD have been found to display diminished sensitivity to protecting their social reputations (Izuma et al 2011). Nevertheless, the use of everyday-type scenarios is undoubtedly of greater ecological validity than more traditional abstract tasks, and the clinical evidence suggests that reduced pro-social behaviour is likely to characterise everyday performance in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Although ASD is associated with impaired social performance, there is relatively little work examining pro-social behaviour in this population. Some evidence from studies of charitable giving suggests that those with ASD donated less and showed reduced preference for charities benefiting other people, as compared to controls (Lin et al 2012), and were less influenced by the presence of an observer (Izuma et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In another relevant study, participants with autism played a modified dictator game in which they chose among options to donate (or not) to charity and did so while observed by others or in private. When observed by others, control participants made increased donation choices, whereas the autism group showed no social facilitation; the groups showed equal performance facilitation when observed during a nonsocial cognitive task, suggesting a specific insensitivity to social reputation in ASD (74). …”
Section: Multiplayer Economic Games Quantify the Behavioral Dynamics mentioning
confidence: 93%
“…It is also associated with altered social cognition [15] and atypical social motivation [11] including social anhedonia [9]. A lack of MD might underpin lower social influence on perceptual [8] and esthetic [11] judgments as well as learning [21] and donation decisions [20] associated with autism. An absence of MD would also compromise the sharing of desires and, hence, result in altered social interaction and possibly idiosyncratic preferences and atypical interests.…”
Section: Introductionmentioning
confidence: 99%